Development and Testing of a Short Scale to Estimate the Importance of Economic, Social and Environmental Sustainability of Fermented Plant-Based Foods - Jean-Paul C. Garin; Federico J. A. Perez-Cueto; Inês Magalhães (Proceedings)
Background and Objectives: The social and economic attitudinal dimensions of sustainability are difficult to estimate and are often overlooked in consumer research. To date, few scales can be used to assess in a combined manner the importance given by consumers to social, economic and environmental sustainability. In the frame of the EU-funded HealthFerm Project, a scale to estimate the relative importance of three dimensions of sustainability was necessary. Therefore, the objective was to develop and test a short scale that would englobe all the keywords that are present in the definition of sustainable development and that would assess the importance of each dimension in the eyes of consumers. Methods: A test-retest reliability study with a sample of volunteers (n = 15) who agreed to fill out the questionnaires twice. Cronbach’s alpha was used to evaluate internal consistency. A paired samples t-test was used to evaluate the repeatability of the scale. Results: Of the 15 respondents, seven were women (46.7%); the mean age was 23.5 years (s.d.: 2.4); 66.7% lived in an urban area and 33.3% in a suburban area; 53.3% had a higher education; 46.7% of the sample described their economic situation as neither easy nor difficult. Regarding their diet, 26.7% were flexitarian, 66.7% omnivore and 6.7% pescetarian. There was no difference (paired samples t-test; p-value > 0.05) between the two time points, indicating that the scale is reliable. Furthermore, the scale showed very good internal consistency (Cronbach’s alpha of 0.98). Conclusion: The short scale can be used to evaluate how important the different dimensions of sustainability of fermented plant-based foods are to consumers.